Pengaruh Konflik Peran dan Wewenang Pekerjaan terhadap Kepuasan Kerja pada Karyawan Satuan Polisi Pamong Praja di Kabupaten Brebes - Lusia Wulandari Sutejo (Sekolah Tinggi Ilmu Ekonomi Widya Manggalia, 2020)
ABSTRACT This study aims to analyze the effect of role conflict and job authority on job satisfaction among Civil Service Police Unit employees in Brebes Regency. The population in this study were all employees using the census method in determining as many as 116 respondents. The analytical tool used is multiple linear regression with partial test equipment (t test) and simultaneous test equipment (F test). The results of the analysis show partially that the role conflict variable has a positive influence on job satisfaction, and partially the job authority variable has a positive influence on job satisfaction. Simultaneously, the variables of role conflict and jobauthority have a positive effect on job satisfaction. Based on the results of the regression coefficient values that the role conflict variable has a more dominant influence on job satisfaction.Keywords: Role Conflict, Job Authority, Job Satisfaction